HR Analytics and Big Data: Transforming Talent Management and Workforce Planning in the Digital Economy - Karsim, K; Loliyani, Rini; Loliyana, Rina; Salma, Nur (Journal of Economics and Management Scienties, 2025)
In the context of accelerating digital transformation, organizations increasingly rely on HR analytics and Big Data to enhance talent management and workforce planning. This study explores how analytics-driven approaches reshape traditional human resource functions by enabling predictive modeling, evidence-based decision-making, and strategic alignment of human capital. Employing a qualitative research design, semi-structured interviews were conducted with twenty HR professionals and senior managers from digitally mature organizations. Thematic analysis revealed six key insights: the strategic integration of HR analytics in talent processes, the application of Big Data in proactive workforce planning, the rise of predictive modeling for performance and retention, challenges in organizational readiness and ethical governance, the influence of data culture on adoption, and the global implications for managing diverse, distributed workforces. Findings highlight that organizations with strong leadership commitment, cross-functional collaboration, and a culture of data literacy are better positioned to unlock the strategic value of HR analytics. Conversely, firms facing technological, ethical, and cultural barriers risk underutilizing these capabilities. This study contributes to the literature by providing empirical evidence of how HR analytics and Big Data facilitate agile, data-driven HR strategies, and offers practical recommendations for advancing workforce intelligence in the digital economy.